2023
DOI: 10.3389/fnut.2023.1274122
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for the prevention and treatment of COVID-19: a rapid systematic review and meta-analysis

Aruba Sohail,
Huzaifa Ahmad Cheema,
Maidah Sohail Mithani
et al.

Abstract: BackgroundAlthough numerous modalities are currently in use for the treatment and prophylaxis of COVID-19, probiotics are a cost-effective alternative that could be used in diverse clinical settings. Hence, we conducted a meta-analysis to investigate the role of probiotics in preventing and treating COVID-19 infection.MethodsWe searched several databases from inception to 30 May 2023 for all randomized controlled trials (RCTs) and comparative observational studies that evaluated probiotics (irrespective of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In addition, metabolites of microbial origin, by acting on the gut-brain axis can influence brain function [83] with favorable effects on mood and sleep; as well as reduced depression, anger and fatigue [84]. Similar benefits were also observed in hospitalized COVID patients, who after receiving probiotic supplementation, especially with Lactobacillus and Bifidobacterium strains [85] had reduced overall symptoms, including lowered inflammatory reactions, decreased the duration of hospitalization and recovery time, what may suggest that probiotics may have potential to reduce mortality resultant from this condition [86].…”
Section: Use Of Probiotic In the Management Of Me/cfs And Long Covid ...mentioning
confidence: 89%
“…In addition, metabolites of microbial origin, by acting on the gut-brain axis can influence brain function [83] with favorable effects on mood and sleep; as well as reduced depression, anger and fatigue [84]. Similar benefits were also observed in hospitalized COVID patients, who after receiving probiotic supplementation, especially with Lactobacillus and Bifidobacterium strains [85] had reduced overall symptoms, including lowered inflammatory reactions, decreased the duration of hospitalization and recovery time, what may suggest that probiotics may have potential to reduce mortality resultant from this condition [86].…”
Section: Use Of Probiotic In the Management Of Me/cfs And Long Covid ...mentioning
confidence: 89%
“…In addition, metabolites of microbial origin, by acting on the gut-brain axis, can influence brain function [85], with favorable effects on mood and sleep and reduced depression, anger and fatigue [86]. Similar benefits were also observed in hospitalized COVID patients, who, after receiving probiotic supplementation, especially with Lactobacillus and Bifidobacterium strains [87], had reduced overall symptoms, including lowered inflammatory reactions, decreased hospitalization duration and recovery time, which may suggest that probiotics may have the potential to reduce mortality resultant from this condition [88].…”
Section: Use Of Probiotic In the Management Of Me/cfs And Long Covid ...mentioning
confidence: 90%
“… 159 , 160 A meta‐analysis found that probiotics shortened the length of hospital stay, recovery time, and reduced the risk of death, suggesting the potential of probiotics as an adjuvant therapy to reduce the risk of death and symptoms in COVID‐19. 161 Based on the gut–lung axis theory, there is a bidirectional interaction between gut microbiota and lung. Probiotics reduce serum C‐reactive protein levels, shorten the length of hospital stay, and further improve respiratory symptoms through the gut–lung axis.…”
Section: Microbiota‐based Implications For Therapeutic Interventionsmentioning
confidence: 99%